2013
DOI: 10.1063/1.4792495
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure study of the structural and elastic properties of defect-chalcopyrite HgGa2Se4

Abstract: In this work, we focus on the study of the structural and elastic properties of mercury digallium selenide (HgGa 2 Se 4) which belongs to the family of AB 2 X 4 ordered-vacancy compounds with tetragonal defect chalcopyrite structure. We have carried out high-pressure x-ray diffraction measurements up to 13.2 GPa. Our measurements have been complemented and compared with total-energy ab initio calculations. The equation of state and the axial compressibilities for the lowpressure phase of HgGa 2 Se 4 have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 74 publications
(95 reference statements)
4
34
0
Order By: Relevance
“…Among other techniques, they have been studied by XRD, being several pressure-induced transitions reported. [6][7][8][9][10][11][12][13][14][15] The reversibility of these transitions is subject of dispute. In some cases, it has been found that the transitions are not reversible, being metastable polymorphs recovered at ambient conditions after decompression.…”
Section: Introductionmentioning
confidence: 99%
“…Among other techniques, they have been studied by XRD, being several pressure-induced transitions reported. [6][7][8][9][10][11][12][13][14][15] The reversibility of these transitions is subject of dispute. In some cases, it has been found that the transitions are not reversible, being metastable polymorphs recovered at ambient conditions after decompression.…”
Section: Introductionmentioning
confidence: 99%
“…The B/G ratios in Table 3 indicate that CGS in P4/mmm and Amm2 are ductile material. The bulk modulus, and elastic constant and B/G ratio calculated from VRH method were widely used to classify type of phase in compounds such as MgCu 2 [31], HgGa 2 Se 4 [32], CdGa 2 Se 4 [33], HgGa 2 Se 4 [34] and HgGa 2 S 4 [35]. Bulk modulus, C 11 , and B/G ratio of CuGaSe 2 increase under high-pressure which related with the defect-chalcopyrite compounds (HgGa 2 Se 4 and HgGa 2 S 4 ) [32,35].…”
Section: Resultsmentioning
confidence: 99%
“…High‐pressure studies of OVCs with A II B 2 III X 4 VI stoichiometry are receiving increasing attention in the last years . The vast majority of these works have been focused on the study of the structural and vibrational properties of A II B 2 III X 4 VI compounds by means of X‐ray diffraction (XRD) and Raman scattering (RS) measurements, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of these works have been focused on the study of the structural and vibrational properties of A II B 2 III X 4 VI compounds by means of X‐ray diffraction (XRD) and Raman scattering (RS) measurements, respectively. In particular, three high‐pressure works have recently reported the structural and vibrational properties of DC‐HgGa 2 Se 4 under pressure where pressure‐induced phase transitions have been observed . The disordered stannite (DS) structure and the disordered rocksalt (DR) structure have been proposed as the high‐pressure phases of DC‐HgGa 2 Se 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation